Estudo do potencial da farinha de Flamboyant-mirim (Caesalpinia pulcherrima) germinada e não germinada como ingrediente funcional em pães - Garcia, Flávia Cristina (2025)
The Flamboyant-Mirim (Caesalpinia pulcherrima) is an ornamental plant with aesthetic and scientific potential, especially regarding the germination of its seeds and their use in the food industry. This study evaluated the effect of seed germination on the biochemical and technological properties of the resulting flours and their application in sandwich bread. The process included soaking the seeds for 24 hours, followed by incubation at 30 °C under fluorescent light for 144 hours, with selection based on the presence or absence of radicle formation. The resulting flours, after seed dehydration, were incorporated into bread at concentrations of 2%, 4%, 6%, 8%, and 10%. The results indicated that flamboyant-mirim germination increased the antioxidant activity and total phenolics of both flours and breads, with a remarkable highlight for breads made with germinated flour, which showed activity up to six times higher than the control. Anthocyanin content decreased with germination, while flavonoids remained stable. Germination proved effective in enhancing the bioactivity and functional value of the breads. Germination also increased the water absorption (3.06 g/g) and swelling power (5.13 g/g) of the flours. In breadmaking, the addition of up to 4% germinated flour preserved the specific volume, expansion factor, and crumb cell structure, whereas higher levels significantly impaired these properties. Color analysis revealed a reduction in lightness and an intensification of reddish tones, more pronounced in non-germinated flours. Micrographs showed that, above 6% addition, both flours hindered gluten network formation and bread porosity. It is concluded that germinated flour exhibits superior technological performance at low concentrations, and its use is recommended at levels up to 4% in fermented bread formulations.